HUBUNGAN LINGKUNGAN RUMAH DAN STATUS IMUNISASI TERHADAP KEJADIAN KASUS CAMPAK PADA BALITA DI DESA HUTAIMBARU KECAMATAN BARUMUN KABUPATEN PADANG LAWAS TAHUN 2013 - amanda yuliana harahap; evi naria; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Measles is an infectious disease highly marked by virus and it may result in a more serious complication, very potential to cause to spread epidemic. In Indonesia, for 2004 nationally, the frequency existing an extra-ordinance occurrence of the Measles itself got on the second rank following DHF with total cases noted 2,818 and caused 44 death or CFR rate of 1.56%. The environment is known as one of factors that it may increase spreading out the measles. The objective of this study is to determine the correlations of the house environmental and the immunisation stated against the occurrence of measles at Desa Hutaimbaru Kecamatan Barumun Kabupaten Padang Lawas for 2013. This study adopted a descriptive survey method with Cross sectional design. The population to this research involved all families living around Desa Hutaimbaru 78 households, the population is 316 people. The sample on this research taken such as family with kids as children five years old and in school aged, included 40 households. Analyzed by uni-variant and bi-variant analysis using Chi Square test. The result of study indicated that there is a correlation on available ventilation with the measles (p = 0.011) and there is correlations between the measles immunisation stated with the measles disease (p = 0.0001). Regarding variable on crowded in people density and about lighting by ventilation has no correlation with the measles on the area. It is suggestible to the local community living around Desa Hutaimbaru, urged to improve the condition of houses environment, to recondition the environmental around at least fulfill the health requirement, still the authority should encourage the parents bring those kids to have immunization in measles preferable while age 6-59 months old and to all kids as going school to SD grade 1 through 6. Keywords : measles, house environment, measles immunisation statue